Determinants of Brand choice of two wheelers in Kathmandu Valley (The International Research Journal of Management Science, 2017)
Understanding of consumer buying behavior is difficult task as it is influenced by many factors such as cultural, social, personal and psychological. Understanding the consumer’s lifestyle is necessary for the marketers. Consumer needs and preferences are changing due to the change in the factors like demographics and lifestyles. These changes can become great business opportunities for alert marketers and threats for those who fail to adapt. Demographic variables help marketers locate their target market and psychographic variables provide the marketer with more insight about the segment. Psychographics is in common lifestyle analysis or AIO (activities, interests and opinions) research.The major objective is to empirically examine the relationship and impacts of demographic and psychographic variables with brand choice. A conceptual model has been tested with different determinants of demographic and psychographic variables to examine relationship with brand choice. In this study, Activities, Interests and Opinions (AIO) is used to identify lifestyle dimensions and demographic variables (age, education level, profession and Gender) as independent variables and brand choice (Innovation, quality, advertising, and price and reference group) as dependent variable. The results indicated that the lifestyle factors and demographic factors have impact on brand choice variables. The study shows that there was a significant association between the lifestyle of the consumers and the brands of products used by them. From the study it was concluded that consumers often choose products, services and activities over other because they are associated with a certain lifestyle.